PENGARUH UKURAN SERBUK TEMPURUNG KELAPA SEBAGAI PENGISI KOMPOSIT POLIESTER TAK JENUH TERHADAP SIFAT MEKANIK DAN PENYERAPAN AIR - Falma Irawati Sijabat; Jenmorisdo Saragih; Halimatuddahliana (Talenta Publisher (Universitas Sumatera Utara), 2013)
Coconut Shell Powder (CSP) was derived from industrial Making Anti-Mosquito can potentially be used as filler in materials composite. The investigation on the utilization of CSP as filler in a polyester matrix has been done with the purpose to obtain the best CSP fillers size in Unsaturated Polyester (UPR) composites in producing the best mechanical properties such as tensile strength, impact strength and water absorption. In this study, UPR was mixed with CSP at the sizes 50 mesh, 70 mesh and 100 mesh with comparison of CSP: Unsaturated Polyester 20:80 (w/w) by using hand lay-up method. The result of mechanical properties showed that, at a ratio of CSP: PE (20:80), the maximum tensile strength obtained is 42.558 MPa with the size of CSP 70 mesh. The test on impact strength was found that the increasing only occured with the size of CSP 100 mesh at 6083.47 J/m2. For absorption test, the highest water absorption occured at the first day, water absorption increased with increasing the amount of filler and the most CSP absorbed water at 70 mesh.